Mining Frequent Itemsets Without Candidate Generation In Machine Learning - et. al., B. Satheesh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mining of regular trends in group action databases, time series databases, and lots of different database types was popularly studied in data processing research. Most previous studies follow the generation-and-test method of associate degree Apriori-like candidate collection. In this study, we seem to propose a particular frequency tree like structure, which is associated degree of prefix-tree like structure that is extended to be used for compressed storage, crucial knowledge of the frequency pattern, associated degrees create an economic FP-tree mining methodology, FP growth, by the growth of pattern fragments for the mining of the entire set of frequent patterns. Three different mining techniques are used to outsize the information which is compressed into small structures such as FP-tree that avoids repetitive information scans, cost. The proposed FP-tree-based mining receives an example philosophy of section creation to stay away from the exorbitant age of several competitor sets, and an apportioning-based, separating and-overcoming technique is used to divide the mining task into a contingent knowledge base for restricted mining designs that effectively reduces the investigation field.